Pelatihan Kesehatan dan Keselamatan Dasar bagi Relawan SAR Masyarakat di Malang Raya: Laporan Pengabdian Masyarakat: Ganif Djuadi, Diniyah Kholidah, Handy Lala, Bernadus Rudy Sunindya, Dimas Dwi, Yoga Saputra, Edi Utomo Putro, Diana Barsasella - Ganif Djuadi; Diniyah Kholidah; Handy Lala; Bernadus Rudy Sunindya; Dimas Dwi; Yoga Saputra; Edi Utomo Putro; Diana Barsasella (Jurnal Persada Husada Indonesia, 2025)
Disaster-prone countries such as Indonesia require well-prepared Search and Rescue (SAR) volunteers, not only in technical rescue skills but also in basic health and safety knowledge. This community service program, conducted by lecturers and students of Poltekkes Kemenkes Malang in collaboration with the Malang Raya SAR Unit, aimed to strengthen volunteer capacity through the â€œBasic Health and Safety Training for SAR Teamsâ€ held on February 8â€“9, 2025. The training included theoretical sessions and practical simulations covering personal protective equipment (PPE) usage, self-care, nutrition, health incident reporting, and insurance literacy. A total of 88 participants, representing the Malang Raya Forum for Coordination of Search and Rescue Potentials (FKP3), completed pre- and post-tests as well as practical evaluations. The results showed a significant increase in participantsâ€™ knowledge (from a pre-test mean of 54.95 Â± 8.22 to a post-test mean of 90.34 Â± 5.69, p < 0.05), with improved consistency reflected in reduced standard deviation values. Observational data confirmed participantsâ€™ enhanced ability in PPE usage, health documentation, and hygiene practices under limited conditions. These findings highlight the effectiveness of integrating health promotion, preventive approaches, and practical simulations in volunteer training. Such interventions are vital to reducing health risks during rescue operations and ensuring safer humanitarian missions. This program may serve as a replicable model for similar community-based SAR training in other disaster-prone regions.